(untitled) (Community Based Medical Journal, 2013)
Prevention of excessive heat loss is fundamental to survival of low birth weight (LBW) newborns. Highly expensive incubator is not available in most of the health care facilities of Bangladesh. Warm cot care by heater or with light bulbs may alternatively help in maintenance of temperature of LBW newborns in health care facilities where incubator is not available. So far i know no such study was conducted before in our country, this study was carried out to show the effectiveness of warm cot care in comparison to incubator care. The present study was cross sectional descriptive type study conducted in the Department of Neonatology, Mymensingh Medical College over a period 1 year from January 2009 to December 2009. Fifty neonates weighing 1200-2000g with gestational age ? 30 weeks to 40 weeks were allocated to an incubator group and similar number with same criteria were taken as cot care group. In cot care group, those babies were selected that are not supposed to cot care due to lack of incubator. The study showed that there were no differences between infants warm cot care versus incubator care. The temperature of the study patients showed that 34(68.0%) and 36(72.0%) maintained normal temperature all the time during hospital stay prior to discharge and rest 16(32.0%) and 14(28.0%) in cot and incubator group respectively became either hypothermic or hyperthermic. Mild hypothermia/cold stress was 7(14.0%) in cot and 4(8.0%) in incubator group. Moderate hypothermia and severe hypothermia was none in both groups. Hyperthermia/fever was 9(18.0%) and 10(20.0%) in cot and incubator group respectively. Analysis reveals that no significant difference was found between two groups. The body temperature of the low birth weight babies (weighing1200-2000g) can be satisfactorily maintained in the low-cost warm cots without the help of incubators which are costly and not available in most of the health care facilities in the developing countries like Bangladesh. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16691 Community Based Medical Journal 2013 July: Vol.02 No 02: 4-8